Polinizadores de canola : perspectivas para o manejo sustentável de insetos, produtividade de grãos e mudanças climáticas - Oliveira, Rosana Halinski de (2017)
The current loss of biodiversity has negative consequences for the environment and impacts several pollination ecossystem services, from which human society benefits directly or indirectly. Among the main pollinators bees, wasps, coleopterans, flies and butterflies stand out. Bees pollinate more than 90% of 107 worldwide crops and other insects might contribute with 20-50% of pollination. Studies about canola (Brassica napus L. cultivar ‗oleífera‘) point out that insect visitation promotes an increase of 12 to 47% in grain productivity. Faced with this, the present work aimed to know the bee, wasp and coleopteran diversity in the canola agroecossystem and identify potential pollinators of the crop. Furthermore, it was evaluated how the landscape and the pollinators influence in the productivity of canola, as well as the habitat suitability for the pollinator species in the face of climatic change in future scenarios (2050). Insects were collected with pan traps in eight fields of B. napus (Hyola 420 and Hyola 61) in the towns of Esmeralda, Estrela and Guarani das Missões, RS, Brazil. For the development of the habitat suitability maps it was used the occurrence records of species in databases and of the canola fields in the towns informed by the crop promoters. Among the wasps the social species Brachygastra lecheguana and Protonectarina sylveirae and the solitary species Campsomeris spp. stand out as potential pollinators. The most representative families of coleopterans were Melyridae, Curculionidae, Nitidulidae, Chrysomelidae and Scarabaeidae, and the most abundant species, which is is polliniferous, with a pubescent body and dense bristles, to which the pollen grains adhere and are transported, thus probably it is a pollinator of canola and surrounding flowers. The productivity of canola was positively influenced by the diversity of social and solitary bees, and the distance from the forest fragment affected the composition of bee guilds present inside the canola fields. It was observed that the semi-natural areas presented a positive correlation with the social native bee species richness. Regarding the category of landscape named ‗Forest‘, it was observed that there is a negative correlation in the 1000 meters radius with the subsocial or solitary bee abundance, possibly explained by their nesting habit, which is mainly underground, which means that it is not exclusively dependent of forest to build their nests. Accordingly, in the ‗Agriculture‘ category, the agricultural landscape in the 1000 meters radius was positively correlated to the abundance of the same guild, fact attributed to the nesting inside canola fields. In view of the different degrees of heterogeneity of the landscape in canola crops, it can be observed that the composition of insects in the canola agroecossystem responds to the ecological and historical factors of each region, being related to the quality of the habitat and food resources for the species. The areas of habitat suitability for canola show a high potential for future crop expansion, however, for this to happen, strategies such as the use of cultivars that have greater tolerance to climatic variables should be established, because they affect plant phenology. In addition, it is suggested to use efforts to introduce the crops in places that are suitable in the future scenario. Furthermore, when comparing the habitat suitability only for canola and then in overlapping with the stingless bee species, we can observe that the appropriate areas increase significantly, reinforcing that for the expansion of the crop, conservation measures of natural and semi-natural habitats for providing food and nesting resources for pollinators are needed.